Globalisation in the time of COVID-19: repositioning Africa to meet the immediate and remote challenges - Sanni Yaya; Akaninyene Otu; Ronald Labonté (BMC, 2020)
Abstract The COVID-19 pandemic has ushered in a new climate of uncertainty which is fuelling protectionism and playing into nationalist narratives. Globalisation is under significant threat as governments scramble to reduce their vulnerability to the virus by limiting global trade and flows of people. With the imposition of border closures and strict migration measures, there have been major disruptions in Africa's global supply chains with adverse impacts on employment and poverty. The African economies overly reliant on single export-orientated industries, such as oil and gas, are expected to be severely hit. This situation is further aggravated by tumbling oil prices and a lowered global demand for African non-oil products. The agricultural sector, which should buffer these shocks, is also being affected by the enforcement of lockdowns which threaten people's livelihoods and food security. Lockdowns may not be the answer in Africa and the issue of public health pandemic response will need to be addressed by enacting context-specific policies which should be implemented in a humane way. In addressing the socioeconomic impact of COVID-19 on African nations, we argue that governments should prioritize social protection programmes to provide people with resources to maintain economic productivity while limiting job losses. International funders are committing assistance to Africa for this purpose, but generally as loans (adding to debt burdens) rather than as grants. G20 agreement so suspend debt payments for a year will help, but is insufficient to fiscal need. Maintaining cross-border trade and cooperation to continue generating public revenues is desirable. New strategies for diversifying African economies and limiting their dependence on external funding by promoting trade with a more regionalised (continental) focus as promoted by the African Continental Free Trade Agreement, while not without limitations, should be explored. While it is premature to judge the final economic and death toll of COVID-19, African leaders' response to the pandemic, and the support they receive from wealthier nations, will determine its eventual outcomes.